2017
DOI: 10.3389/fnmol.2017.00324
|View full text |Cite
|
Sign up to set email alerts
|

CHL1 Is Expressed and Functions as a Malignancy Promoter in Glioma Cells

Abstract: The cell adhesion molecule with homology to L1CAM (close homolog of L1) (CHL1) is a member of the cell adhesion molecule L1 (L1CAM) gene family. Although CHL1 expression and function have been reported in several tumors, the roles of CHL1 in the development of glioma remain unclear. In the present study, we investigated the effects of CHL1 on proliferation indexes and activation of Akt1 and Erk signaling by siRNA in U-87 MG human glioblastoma and human U251 and SHG-44 glioma cells. We found that siRNA targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…Blocking the MAPK/ERK signaling pathway can inhibit the progression of glioma (39). Our previous study demonstrated a positive association between the expression levels of CHL1 and Akt1 activation with no significant effect of CHL1 on ERK1/2 activation (28). In the present study, both NRG1α and β isoforms were reported to activate the ERK signaling pathway.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Blocking the MAPK/ERK signaling pathway can inhibit the progression of glioma (39). Our previous study demonstrated a positive association between the expression levels of CHL1 and Akt1 activation with no significant effect of CHL1 on ERK1/2 activation (28). In the present study, both NRG1α and β isoforms were reported to activate the ERK signaling pathway.…”
Section: Discussionsupporting
confidence: 55%
“…In previous research, CHL1 was found to function as a tumor suppressor during primary tumor growth (27) and it was reported that CHL1 expression levels were decreased in human breast cancer with a low malignancy grade (27), whereas downregulation of CHL1 expression levels by the targeting of microRNA (miR)-10a enhanced the migration and invasion properties of human cervical cancer cells (20). In contrast to these diverse findings regarding CHL1 in most types of cancer, our previous research revealed that CHL1 functions in promoting cell proliferation, metastasis and migration of human glioma cells both in vitro and in vivo, suggesting a positive association between CHL1 level and glioma grade (28).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, CHL1 was reported promoting cell proliferation, metastasis and migration in human glioma (Yang et al 2017). As for research on CHL1 and tumor chemoresistance rarely have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…ERK is a member of MAPK family that is involved in many cellular functions, including cell growth, differentiation, survival and apoptosis ( Sebolt-Leopold and Herrera, 2004 ). AKT is a key component in the PI3K pathway involved in cell survival, growth and cell apoptosis ( Engelman, 2009 ; Pan et al, 2015 ; Yang et al, 2017 ). Our results showed that the levels of both p-AKT and p- ERK1/2 were decreased in response to trimebutine.…”
Section: Discussionmentioning
confidence: 99%